Elimination of BMP7 from the developing limb mesenchyme leads to articular cartilage degeneration and synovial inflammation with increased age. Issue 11 (15th April 2015) - Abula, Kahaer; Muneta, Takeshi; Miyatake, Kazumasa; Yamada, Jun; Matsukura, Yu; Inoue, Makiko; Sekiya, Ichiro; Graf, Daniel; Economides, Aris N.; Rosen, Vicki; Tsuji, Kunikazu
Abstract : While osteo‐ and chondro‐inductive activities of recombinant human bone morphogenetic protein 7 are well established, evaluation of the role of endogenous BMP7 in skeletal homeostasis has been hampered by perinatal lethality in BMP7 knockout mice. Here, we examined physiological roles of endogenous BMP7 in joint homeostasis and showed that proteoglycan contents in articular cartilage were significantly reduced in the absence of BMP7. Loss of BMP7 did not affect survival of articular cartilage cells, but resulted in reduced expression of aggrecan and enhanced expression of matrix metalloproteinase 13. We also found extensive synovial hyperplasia and enhanced expression of Activin A. These findings suggest that locally produced BMP7 is prerequisite for postnatal synovial joint homeostasis and may be involved in osteoarthritic changes in adults. Abstract : Physiological roles of BMP7 in joint formation and homeostasis were examined. Loss of BMP7 did not affect joint formation. Proteoglycan contents were reduced in articular cartilage null for BMP7. Extensive synovial hyperplasia was observed in the knee joint in the absence of BMP7. Loss of BMP7 did not affect chondrocyte survival.